Studying the Impact of the DDB2 T338M Missense Mutation on the Development of Equine Squamous Cell Carcinoma and Sarcoid - Hannah Quatember; Barbara Nell; Barbara Richter; Doris Rigler; Marlies Dolezal; Sabine Sykora; Barbara Wallner (Animals)
A missense mutation in damage-specific DNA binding protein 2 (DDB2 c.1013 C>T; p.Thr338Met) has been described as a risk factor for ocular squamous cell carcinoma (OSCC) in the Haflinger breed. Here, we examined the impact of DDB2 C>T allele status on the development of OSCC, squamous cell carcinoma (SCC) at other localisations, or equine sarcoid (ES) in Haflingers and other breeds with a high incidence of these tumour types. We genotyped affected Haflinger, Noriker, Warmblood, and Icelandic horses. Results based on 56 Haflingers confirmed the significantly higher risk for OSCC in DDB2-TT Haflingers but also suggested an increased risk in heterozygous (DDB2-CT) Haflingers. We also found the DDB2-T allele in Norikers with OSCC but not in Warmbloods. Only one homozygous DDB2-T allele carrier was among the 23 Haflinger and 44 Noriker/Warmblood/Icelandic horses with an SCC at a localisation other than the eye or ES. Overall, our data underline the severity of the DDB2-T allele with regard to OSCC and provide no evidence for the impact of the DDB2 risk allele status on the development of ES and SCC at localisations other than the eye.